Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

You can simplify it. Or just this one...

1. Cube the first term.

2. Three times the square of the first term and the second term.

3. Three times the first terms and the square of the second term

4. Cube of the second term.

For example:

(a+b)³ =

(a-b)³ =

(4b+3)³ =

1. Cube the first term.

2. Three times the square of the first term and the second term.

3. Three times the first terms and the square of the second term

4. Cube of the second term.

For example:

(a+b)³ =

(a-b)³ =

(4b+3)³ =

(a + b)³ = (a + b) (a + b) (a + b)

= a³ + 3a²b + 3ab² + b³

Steps in finding the special product of (a + b)³ :

a) Cube the first term, a =

**a³**

b) Three (first term)² (last term) = 3 (a)² (b) =

**3a²b**

c) Three (first term) (last term)² = 3 (a) (b)² =

**3ab²**

d) Cube the last term =

**b³**

Combine the results, the special product is:

a³ + 3a²b + 3ab³ + b³